The Life Between Big Data Log Events - George Veletsianos; Justin Reich; Laura A. Pasquini (SAGE Publishing, 2016)
Big data from massive open online courses (MOOCs) have enabled researchers to examine learning processes at almost infinite levels of granularity. Yet, such data sets do not track every important element in the learning process. Many strategies that MOOC learners use to overcome learning challenges are not captured in clickstream and log data. In this study, we interviewed 92 MOOC learners to better understand their worlds, investigate possible mechanisms of student attrition, and extend conversations about the use of big data in education. Findings reveal three important domains of the experience of MOOC students that are absent from MOOC tracking logs: the practices at learners' workstations, learners' activities online but off-platform, and the wider social context of their lives beyond the MOOC. These findings enrich our understanding of learner agency in MOOCs, clarify the spaces in-between recorded tracking log events, and challenge the view that MOOC learners are disembodied autodidacts.